Evaluasi Kinerja Biaya dan Waktu Menggunakan Metode Earned Value pada Proyek Pembangunan Gedung di Polresta Palangka Raya - Zachry, Hatara; Nuswantoro, Waluyo; Happy Puspasari, Veronika (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2025)
In project implementation, management of cost, time, and quality must be carried out carefully to ensure project completion is in accordance with the schedule and budget that has been set. As a project funded by the government, project implementers are expected to be able to manage the budget efficiently. The construction project for the Palangka Raya City Police Detention Center and Narcotics Unit Building, with a contract value of Rp. 4,654,035,594.00 with an implementation duration of 150 working days, starting from June 21 to November 17, 2024. However, in the 13th week of implementation, the project progress was recorded at 41.22%, with a deviation of 1.46%, while the target progress that should have been achieved was 42.67%. This study aims to evaluate the cost and time performance during project implementation. The results of the cost performance evaluation showed that the ACWP in the 19th week was Rp3,381,386,536.73, lower than the BCWP of Rp3,611,321,688.70. Consistently positive CV values ​​and CPI values ​​that are always more than 1 indicate good cost efficiency. The remaining cost projection for project completion is Rp.976,323,646.85, so the total project completion cost is estimated at Rp.4,357,710,183.58, with a surplus of Rp.296,325,410.42 from the contract budget. Time performance evaluation, in the 19th week the negative SV value of -Rp.206,811,358.25 and SPI of 0.946 indicate project delays. The average CR value> 1 indicates that overall project performance in terms of cost and time is still in the good category. The time projection for the remaining work to complete the project is 17.974 days, with a total completion time of 150.974 days, exceeding the planned schedule with a delay of 0.974 days rounded up to 1 day